Peripheral adenomatoid odontogenic tumor: report of a rare case - Rakesh Kumar; Rajeev K Singh; Ramesh K Pandey; Shadab Mohammad (Elsevier, 2012)
ABSTRACT: Adenomatoid odontogenic tumor is a benign odontogenic tumor with slow growth potential and exceptionally low recurrence rate. The tumor is predominantly found in females in the second decade of life, involving the maxilla more frequently than the mandible. The tumor presents in three variants-intrafollicular, extrafollicular, and peripheral. The peripheral variant is very rare and only few reports have been published. We present a rare case of peripheral adenomatoid odontogenic tumor in a 10-year-old male child in the anterior region of the mandible.